FDX2 and ISCU Gene Variations Lead to Rhabdomyolysis With Distinct Severity and Iron Regulation. (19th February 2022) - Montealegre, Sebastian; Lebigot, Elise; Debruge, Hugo; Romero, Norma; Héron, Bénédicte; Gaignard, Pauline; Legendre, Antoine; Imbard, Apolline; Gobin, Stéphanie; Lacène, Emmanuelle; Nusbaum, Patrick; Hubas, Arnaud; et al.
Abstract : Background and Objectives: To determine common clinical and biological traits in 2 individuals with variants in ISCU and FDX2, displaying severe and recurrent rhabdomyolyses and lactic acidosis. Methods: We performed a clinical characterization of 2 distinct individuals with biallelic ISCU or FDX2 variants from 2 separate families and a biological characterization with muscle and cells from those patients. Results: The individual with FDX2 variants was clinically more affected than the individual with ISCU variants. Affected FDX2 individual fibroblasts and myoblasts showed reduced oxygen consumption rates and mitochondrial complex I and PDHc activities, associated with high levels of blood FGF21. ISCU individual fibroblasts showed no oxidative phosphorylation deficiency and moderate increase of blood FGF21 levels relative to controls. The severity of the FDX2 individual was not due to dysfunctional autophagy. Iron was excessively accumulated in ISCU-deficient skeletal muscle, which was accompanied by a downregulation of IRP1 and mitoferrin2 genes and an upregulation of frataxin ( FXN ) gene expression. This excessive iron accumulation was absent from FDX2 affected muscle and could not be correlated with variable gene expression in muscle cells. Discussion: We conclude that FDX2 and ISCU variants result in a similar muscle phenotype, that differ in severity and skeletal muscle iron accumulation. ISCU and FDX2 are not involved in mitochondrial iron influx contrary to frataxin.